The Effect of Game-Based Learning through an Escape Room on Mathematical Critical Thinking Skills - Sasella Noveria; Nina Agustyaningrum; Dita Aldila Krisma (Kognisi: Jurnal Ilmu Keguruan, 2026)
This study was motivated by the low level of critical thinking skills among students in mathematics learning. The study aims to determine the differences in critical thinking skills between students who learn using a game-based learning model through an escape room game and those who learn through direct instruction, as well as to analyze the improvement in critical thinking skills before and after the intervention. This study employs a quantitative approach using a quasi-experimental design. The sample was selected using cluster random sampling, involving an experimental class and a control class. Data collection was conducted through critical thinking ability tests in the form of pre-test and post-test. Data analysis utilized the Mann-Whitney U test, the Wilcoxon Signed Rank test, N-Gain, and Effect Size. The results indicate a significant difference in the improvement of critical thinking skills between the experimental class and the control class (Z=-2.82; p<0.05). Additionally, there was a significant improvement in the experimental class before and after the intervention (Z=-4.52; p<0.05). The N-Gain value of  falls into the low category, while the Effect Size value of  indicates a high effect. Thus, the game-based learning model through an escape room game influences the improvement of students’ critical thinking skills and can be used as an alternative learning method that fosters critical thinking in mathematics education.